The Study Analysis of Chinese Idiom Learning at Indonesian High School - Lestari Puspita Ningsih; Jin Xiaoyan (Linguistic, English Education and Art (LEEA) Journal, 2020)
This study is aimed to determine the effectiveness of the application of learning Chinese Idiom at school. This also recognized the mastery of Mandarin language teachers in Chinese Idiom. This research is used a quantitative descriptive method. Based on the results of surveys and tests that have been carried out it is known that there are still many schools that do not implement Mandarin language learning for basic competencies with the Chinese Idiom material. It can be concluded that the application of basic competencies related to Mandarin idioms is still ineffective. Thus in order for Chinese Idiom learning to be carried out properly, it is necessary to carry out the following matters, including teaching materials development, language teaching methodologies development, professional Mandarin language teacher’s development, the development of adequate Mandarin learning facilities. Keywords: Chinese Idiom, Teaching Chinese as a Foreign Language, Indonesian High School,Chinese Curriculum